Van eaudiobook - Bennett, Sawyer (Cold Fury Hockey, 2017)
As one of the league's toughest enforcers, Van Turner is ruthless on the ice. He plays hard because it's the only way to channel the rage boiling inside, and a reputation as an A-hole is better than everyone knowing the truth. Van has spent his entire life running from a secret that's kept him from getting involved in relationships—or accepting lucrative deals with East Coast teams. Then the Carolina Cold Fury makes him an offer he can't refuse . . . and Van meets a woman he can't resist. Simone Fournier is the stubborn one in her family—and that's saying something, considering her brothers are two of the Cold Fury's biggest stars. Simone gets what she wants, and what she wants is Van. Still, there's a part of him Simone can't reach, no matter how hard she tries. In private, he's all fire and passion. In public, he freezes her out. Van may want to push her away, but Simone won't let him go that easily. Because this time, she's playing for keeps. Contains mature themes.